2019
DOI: 10.3390/nano9070943
|View full text |Cite
|
Sign up to set email alerts
|

SPIONs Prepared in Air through Improved Synthesis Methodology: The Influence of γ-Fe2O3/Fe3O4 Ratio and Coating Composition on Magnetic Properties

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) have shown great potential in biomedicine due to their high intrinsic magnetization behaviour. These are small particles of magnetite or maghemite, and when coated, their surface oxidation is prevented, their aggregation tendency is reduced, their dispersity is improved, and the stability and blood circulation time are increased, which are mandatory requirements in biomedical applications. In this work, SPIONs were synthesized in air through a reduction-preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 46 publications
4
20
0
Order By: Relevance
“…Previous studies [ 1 ] have shown that their unique properties such as high surface area to volume ratios and superparamagnetism (exhibited by particles with a diameter below 30 nm) [ 4 , 5 ] make them suitable for various applications. Therefore, due to their capability to be easily magnetized when they are exposed to the action of an external magnetic field, SPION could be used in various biomedical applications such as: drug and gene delivery [ 6 , 7 ] chelation therapy [ 8 ], hyperthermia [ 9 , 10 ], tissue repair [ 11 , 12 ], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [ 1 ] have shown that their unique properties such as high surface area to volume ratios and superparamagnetism (exhibited by particles with a diameter below 30 nm) [ 4 , 5 ] make them suitable for various applications. Therefore, due to their capability to be easily magnetized when they are exposed to the action of an external magnetic field, SPION could be used in various biomedical applications such as: drug and gene delivery [ 6 , 7 ] chelation therapy [ 8 ], hyperthermia [ 9 , 10 ], tissue repair [ 11 , 12 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In general, to prevent the agglomeration of nanoparticles and to improve their colloidal stability and biological properties, they are incorporated into polymers (chitosan, dextran, poly(vinyl alcohol)—PVA, gelatin, polyvinylpyrrolidone (PVP), etc.) [ 6 , 13 , 14 , 15 , 16 ]. Dextran, (H(C 6 H 10 O 5 )xOH), is one of the most widely used natural polysaccharides used as a coating for SPION [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sp-GAC showed a major IR shift in the lowfrequency region around 510 cm -1 -570 cm -1 . This is the characteristic vibration of Fe-O-Fe from iron oxide nanoparticles [51]. Therefore, this stated the successful impregnation of iron oxide onto Sp-GAC.…”
Section: Characterization Of Spions Impregnated Activated Carbonmentioning
confidence: 77%
“…The polymeric materials together with their mono- and co-polymeric entities, have been utilized for in vitro cancer cell lines and in vivo cancer sites drug delivery with the aims of providing stability, transport feasibility, efficient drug targeting, drug deloading at the site, and removal/excretion of residual products, metabolites, and byproducts [ 22 ].…”
Section: Dox Delivery: Spions’ Polymeric Monomeric and Miscellaneous ...mentioning
confidence: 99%